COMPARING THE EFFECTS OF MODIFIED EPLEY'S MANEUVER AND CAWTHORNE– COOKSEY EXERCISE WITH BRANDT –DAROFF EXERCISE IN BENIGN PAROXYSMAL POSITIONAL VERTIGO - S. DIVYA,; R. ARUNACHALAM,; A. KUMARESAN,; S. KIRUTHIKA, (International Journal of Pharma and Bio Sciences, 2016)
Benign Paroxysmal Positional Vertigo (BPPV) is the most common cause of vertigo constituting 20% - 40% of all patients with peripheral vestibular disease in which the posterior canal is usually affected. To determine and evaluate whether the effect of combined therapy will improve the balance confidence in posterior canal Benign Paroxysmal Positional Vertigo. In this experimental design a total of 30 subjects with an average age of 35 – 65 years of females those who had dizziness and balance disorder were assessed with Activities–Specific Balance Confidence scale (ABC) and Dizziness Handicap Inventory (DHI). 30 subjects were randomly allocated into Experimental group (15 Subjects) who received Modified Epley’s maneuver and Cawthorne–Cooksey exercise with medications and Control group (15 subects) Brandt –Daroff exercise with medications. At the end of the treatment, ABC scale and DHI scale on comparison within and between the experimental group revealed extremely statistically significant result with pre-test and post-test mean of p value < 0.0001 whereas the control group revealed not statistically significant result with pre-test and post-test mean of p value 0.30 and 0.15 respectively.